(untitled) (Journal of International Studies, 2025)
Amidst shifting security dynamics in East Asia, Japan faces an evolving strategic landscape, particularly in response to mounting threats from North Korea and China. Through a descriptive analysis of primary and secondary sources, this study investigates Japan’s trajectory towards potential constitutional amendment and further militarization, with a focus on Article 9—a key provision renouncing the use of force and restricting military capabilities. By tracing historical contexts and the U.S.-Japan security alliance, the paper explores Japan’s post-war pacifism and the gradual evolution of its Self-Defense Forces (SDF) within constitutional constraints. Despite inherent constraints, Japan has developed a robust military force, challenging traditional perceptions of its rearmament. While the nation has incrementally expanded its defense posture, legal and political obstacles remain, necessitating constitutional revisions to align its military strategy with contemporary security challenges. Externally, Japan faces threats such as North Korea’s nuclear ambitions and China’s assertive regional policies, while internally, public sentiment, historical legacies, and legal obstacles shape the discourse on constitutional reform. Japan’s path towards constitutional amendment hinges on regional security dynamics and the strength of the U.S.-Japan alliance. The extent of US commitment to regional stability and its capacity to address Japanese security concerns may significantly determine the pace and direction of Japan’s defense normalization. Although Japan is militarily prepared to address emerging security threats, its constitutional constraints persist as a legal challenge. Findings indicate that through a series of incremental military policies, Japan has effectively rearmed itself with credible self-defense capabilities, despite the continued legal restrictions imposed by its pacifist constitution.